Assessment of salivary cortisol level as stress biomarker in anxious pediatric dental patient before and after sandalwood aromatherapy: A randomized clinical trial - Simran Bhojwani (Bioinformation, 2026)
Dental anxiety in children remains a significant clinical problem that can negatively affect behavior, treatment acceptance and overall dental care outcomes. Sandalwood (Santalum album) aromatherapy is a promising nonpharmacological approach to alleviate dental anxiety in children. The study was a randomized controlled trial with 50 children aged 6–9 years, allocated into Group I (sandalwood aromatherapy) and Group II (control). The Venham Picture Scale was used to assess anxiety, and salivary cortisol levels were measured pre- and post-treatment using ELISA. Anxiety scores decreased in both groups, whereas the reduction in salivary cortisol was significantly greater in the sandalwood group (p < 0.001). Thus, data shows that sandalwood aromatherapy effectively reduces physiological stress and may serve as a safe adjunctive strategy for managing dental anxiety in children.